2000
DOI: 10.1007/s002130000451
|View full text |Cite
|
Sign up to set email alerts
|

Leftward shift in the acquisition of cocaine self-administration in isolation-reared rats: relationship to extracellular levels of dopamine, serotonin and glutamate in the nucleus accumbens and amygdala-striatal FOS expression

Abstract: These data are consistent with the hypothesis that isolation rearing produces enduring changes in the sensitivity of dopamine-mediated functions in amygdala-striatal circuitry that may be directly related to the altered reinforcing properties of cocaine and other psychomotor stimulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
125
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 58 publications
(78 reference statements)
16
125
2
1
Order By: Relevance
“…Moreover, the enhanced dopamine response to cocaine produced by PNS is similar to that reported in neonatal isolates (Kehoe et al, 1996;Kosten et al, 2004aKosten et al, , 2003Kosten et al, , 2005Kosten et al, , 2006; see also Howes et al, 2000 for similar results following juvenile isolation) or in rodents subjected to neonatal anoxia (Juarez et al, 2003) in response to other psychomotor stimulant drugs. Neonatal isolates also show a reduction in NAC serotonin (Kosten et al, 2004b) similar to that observed in the present study in PNS rats.…”
Section: Influence Of Pns On Neurochemical Responses To Cocainesupporting
confidence: 78%
“…Moreover, the enhanced dopamine response to cocaine produced by PNS is similar to that reported in neonatal isolates (Kehoe et al, 1996;Kosten et al, 2004aKosten et al, , 2003Kosten et al, , 2005Kosten et al, , 2006; see also Howes et al, 2000 for similar results following juvenile isolation) or in rodents subjected to neonatal anoxia (Juarez et al, 2003) in response to other psychomotor stimulant drugs. Neonatal isolates also show a reduction in NAC serotonin (Kosten et al, 2004b) similar to that observed in the present study in PNS rats.…”
Section: Influence Of Pns On Neurochemical Responses To Cocainesupporting
confidence: 78%
“…Furthermore, direct stimulation of USVs by injection of quinpirole into the shell of the nucleus accumbens is mediated in a complex triphasic way by both dopamine D2 and D3 receptors (Brudzynski et al, 2012). Social isolation (without neonatal PCP) has been shown to increase basal dopamine release in the nucleus accumbens and enhance release in response to amphetamine (Hall et al, 1998), cocaine (Howes et al, 2000) and emotional stimuli (Fulford and Marsden, 1998). Thus the increase in USVs seen in PCP/isolated rats might represent an enhanced response resulting from the priming of the dopaminergic mesolimbic system.…”
Section: Discussionmentioning
confidence: 99%
“…infusion) is used (Bardo et al, 2001). IC rats also display a leftward shift in the cocaine dose response curve compared with SC rats (Howes et al, 2000), indicating that isolation housing enhances sensitivity to stimulant reinforcement compared with social housing. However, the presence of novel objects also plays a role, as the behavioral responses to stimulants, opiates, and alcohol differ between SC and EC animals (Bardo et al, 2001;Green et al, 2003;Coolon and Cain, 2009;El Rawas et al, 2009;de Carvalho et al, 2010).…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 95%
“…In contrast, IC rats have increased amphetamine-stimulated levels of extracellular dopamine in striatum and the nucleus accumbens using in vivo microdialysis compared with SC rats (Jones et al, 1992), although this effect is not obtained under chloral hydrate anesthesia . IC rats also show greater cocaine-stimulated release of accumbal dopamine and greater alterations in the immediate-early genes c-fos and zif-268 in striatum and the central nucleus of the amygdala and, in some cases, in the nucleus accumbens and frontal cortex (Howes et al, 2000;Solinas et al, 2009;Thiel et al, 2010). Housing-induced differences in neurochemical response to stimulant drugs do not likely reflect pharmacokinetic changes, as brain levels of [ 3 H]amphetamine are similar in IC and EC rats after systemic injection .…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 96%